ALTERNATIVE ENERGY RESOURCES AS AN OBJECT OF MAPPING - АГАПОВА, О. Л. (Man and Environment. Issues of Neoecology)
The article highlights the problems of formation of conceptual and terminological apparatus in the field of alternative energy. Attempts to improve and systematize the basic terms and concepts in the industry were made. Inconsistencies and ambiguities in the interpretation of such concepts as «alternative energy resources», «non-conventional energy resources», «renewable energy resources», «energy sources», «energy resources», and «energy potential» were eliminated. Classification of energy resources based on the criteria of depletion, renewability, tradition of usage, and their origin was proposed. The structure of the object of mapping, according to the needs of alternative energy, is considered. The thematic content of cartographic products was determined. Mapping indicators of alternative energy resources; the current state of alternative energy development; environmental, social and economic factors that contribute to the development of the industry or limiting its development were identified.